Decision Making for Selection of Transarterial Locoregional Therapy of Metastatic Neuroendocrine Tumors - Gaba, Ron C.; Mendoza-Elias, Nasya; Morrison, Joseph D.; Valeshabad, Ali Kord; Lipnik, Andrew J. (Seminars in Interventional Radiology, 2017)
Transarterial locoregional therapies (LRTs) are indispensable components of the modern interventional oncologic therapy of liver-dominant metastatic neuroendocrine tumors (NETs). The scope of available LRTs and their nuanced differences mandates a thorough understanding of their relative applicability and effectiveness in certain clinical circumstances to prescribe appropriate, patient-specific, image-guided therapy. This article aims to provide an overview of transarterial LRT options for liver-dominant metastatic NETs and therapy selection by reviewing procedure types, their advantages and disadvantages, and comparative efficacy in common case scenarios.
Keywords: neuroendocrine tumor; metastatic; locoregional therapy; Interventional radiology